2021
DOI: 10.21608/ejh.2021.82185.1512
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selenium Nanoparticles on Tramadol Induced Hepatotoxicity in a Rat Model

Abstract: Introduction: Selenium nanoparticles (SeNPs) are a promising modality of treatment for various oxidative stress induced and inflammatory diseases. Tramadol (TD) has become the most commonly prescribed opiate with a high liability for addiction, predisposing the liver to oxidative stress induced hepatotoxicity. Aim of the Work:This study aimed to clarify the impact of SeNPs on biochemical and histological alterations induced by TD. Materials and Methods: Sixty rats were divided into four groups: Group I: (Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported that SeNPs reduced Tramadol-induced liver damage by reducing oxidative stress and improving antioxidant enzyme activities. Moreover, SeNPs significantly decreased liver enzyme levels while significantly raising total protein and albumin levels, indicating a protective effect on the hepatocellular membrane [39].…”
Section: Well-dispersible Nanoparticles (Sps-senps) [6 and 22]mentioning
confidence: 91%
“…Previous studies reported that SeNPs reduced Tramadol-induced liver damage by reducing oxidative stress and improving antioxidant enzyme activities. Moreover, SeNPs significantly decreased liver enzyme levels while significantly raising total protein and albumin levels, indicating a protective effect on the hepatocellular membrane [39].…”
Section: Well-dispersible Nanoparticles (Sps-senps) [6 and 22]mentioning
confidence: 91%